Alveolar ridge augmentation with 3D‐printed synthetic bone blocks: A clinical case series. Issue 4 (23rd April 2023) - Perez, Alexandre; Lazzarotto, Benjamin; Marger, Laurine; Durual, Stéphane
Abstract: This report documents the clinical and histological outcome of 3D‐printed calcium phosphate blocks placed in two‐stage procedures to successfully rehabilitate atrophic alveolar ridges. This approach yielded a functionally favorable result. Histological evaluations were performed after healing periods of 6 months and showed ongoing bone regeneration and sprouting capillaries. Abstract : 3D‐printing of alloplastic bone blocks is an efficient approach to successfully rehabilitate atrophic alveolar ridges. It may ideally be extended to custom‐printed scaffolds in order to closely match the defect's morphology.